Low-dose, high-resolution CT of infant-sized lungs via propagation-based phase contrast - James A. Pollock; Kaye Morgan; Linda C. P. Croton; Emily J. Pryor; Kelly J. Crossley; Christopher J. Hall; Daniel Häusermann; Anton Maksimenko; Stuart B. Hooper; Marcus J. Kitchen (Scientific Reports)
Abstract Many lung diseases require high-resolution imaging for accurate diagnosis and treatment. Computed tomography (CT) is the gold-standard technique for non-invasive lung disease detection, but it presents a risk to the patient through the relatively high ionising radiation dose required. Utilising the X-ray phase information has demonstrated improvements in image quality over absorption contrast in small animal models, at equal or lower radiation levels. Propagation-based phase-contrast imaging requires only a spatially coherent wavefield and some propagation between the sample and detector, making it well suited for medical applications. In particular, lung imaging significantly benefits from the strong phase gradients introduced by the lung-air material interfaces. Herein, propagation-based phase contrast CT is demonstrated stepping up to large animals, namely lambs, as a model for paediatric patients, using monochromatic radiation and a photon-counting detector. The resulting CT images demonstrate superior resolution to existing high-resolution CT systems, and push dose to the quantum limit to comply with current Australian guidelines for infant chest CT exposure of $$<2.5\,\text {mSv}$$ effective dose. Constituent raw projections are shown to have significant proportions of pixels with zero photon counts that would create severe information loss in conventional CT. Phase retrieval enabled clear visualisation of minor lung airways ( $$\ge {290}\,{{\upmu }\hbox {m}}$$ ) at doses up to 1225 ± 31% times lower than conventional CT reconstruction and a voxel size of just 75  $${{\upmu }\hbox {m}}$$ .